2020
DOI: 10.1002/joc.6796
|View full text |Cite
|
Sign up to set email alerts
|

Combined impacts of the El Niño‐Southern Oscillation and Pacific Decadal Oscillation on global droughts assessed using the standardized precipitation evapotranspiration index

Abstract: Using the standardized precipitation evapotranspiration index, this study examines the combined effects of El Niño-Southern Oscillation (ENSO) and Pacific Decadal Oscillation (PDO) on global droughts in terms of magnitude, timing, and duration. The ENSO-affected drought hotspots are identified based on drought magnitude and probability of occurrence: five hotspots for El Niño (Amazon, India, central China, Indonesia, and eastern Australia) and four hotspots for La Niña (southeastern United States, southern Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 73 publications
(132 reference statements)
1
20
0
Order By: Relevance
“…Figure 4 a shows consistency with Chen et al 14 , showing that 2015–2016 El Niño causes drought, but La Niña (2010–2011) disagrees with the observation. The observed TWS shows the increase in 2011–2012 when the La Niña is weaker than 2010–2011, and it agrees with the previous studies 41 , 42 ; the LF mode (or PDO) intensifies the increase of TWS. Basin-wide comparisons are complicated because the dynamic spatial variance presented in this region creates difficulties in explaining the regional TWS using an ENSO index.…”
Section: Resultssupporting
confidence: 91%
“…Figure 4 a shows consistency with Chen et al 14 , showing that 2015–2016 El Niño causes drought, but La Niña (2010–2011) disagrees with the observation. The observed TWS shows the increase in 2011–2012 when the La Niña is weaker than 2010–2011, and it agrees with the previous studies 41 , 42 ; the LF mode (or PDO) intensifies the increase of TWS. Basin-wide comparisons are complicated because the dynamic spatial variance presented in this region creates difficulties in explaining the regional TWS using an ENSO index.…”
Section: Resultssupporting
confidence: 91%
“…(2001) showed that most of the large fires in Alaska occurred during moderate to strong El Niño events. During El Niño events, temperatures are typically near normal in western Alaska and often much warmer in southeastern Alaska (Hess et al., 2001; Nguyen et al., 2021; Papineau, 2001). In addition, Hess et al.…”
Section: Resultsmentioning
confidence: 99%
“…The SPEI package requires long term temperature (maximum and minimum) and rainfall data. The SPEI has been employed in many drought studies and has been found suitable [8,37,38,39,40]. To estimate the value of SPEI, the variation in water balance is normalized as log-logistic probability distribution.…”
Section: Standard Precipitation Evapotranspiration Index (Spei)mentioning
confidence: 99%